IMAGING AND MEASUREMENT OF THE PRERETINAL SPACE IN VITREOMACULAR ADHESION AND VITREOMACULAR TRACTION BY A NEW SPECTRAL DOMAIN OPTICAL COHERENCE TOMOGRAPHY ANALYSIS. Issue 10 (October 2017) - Stopa, Marcin; Marciniak, Elżbieta; Rakowicz, Piotr; Stankiewicz, Agnieszka; Marciniak, Tomasz; Dąbrowski, Adam
Abstract : Purpose: To evaluate a new method for volumetric imaging of the preretinal space (also known as the subhyaloid, subcortical, or retrocortical space) and investigate differences in preretinal space volume in vitreomacular adhesion (VMA) and vitreomacular traction (VMT). Methods: Nine patients with VMA and 13 with VMT were prospectively evaluated. Automatic inner limiting membrane line segmentation, which exploits graph search theory implementation, and posterior cortical vitreous line segmentation were performed on 141 horizontal spectral domain optical coherence tomography B-scans per patient. Vertical distances (depths) between the posterior cortical vitreous and inner limiting membrane lines were calculated for each optical coherence tomography B-scan acquired. The derived distances were merged and visualized as a color depth map that represented the preretinal space between the posterior surface of the hyaloid and the anterior surface of the retina. The early treatment d retinopathy study macular map was overlaid onto final virtual maps, and preretinal space volumes were calculated for each early treatment diabetic retinopathy study map sector. Results: Volumetric maps representing preretinal space volumes were created for each patient in the VMA and VMT groups. Preretinal space volumes were larger in all early treatment diabetic retinopathy study map macular regions in the VMT group compared with those in the VMA group. The differences reached statistical significance in all early treatment diabetic retinopathy study sectors, except for the superior outer macula and temporal outer macula where significance values were P = 0.05 and P = 0.08, respectively. Overall, the relative differences in preretinal space volumes between the VMT and VMA groups varied from 2.7 to 4.3 in inner regions and 1.8 to 2.9 in outer regions. Conclusion: Our study provides evidence of significant differences in preretinal space volume between eyes with VMA and those with VMT. This may be useful not only in the investigation of preretinal space properties in VMA and VMT, but also in other conditions, such as age-related macular degeneration, diabetic retinopathy, and central retinal vein occlusion. Abstract : The preretinal space, which is the cavity delineated by the posterior cortical vitreous and the retinal surface, has not been studied in much detail in any pathology. Herein, a novel method for imaging and measurement of the preretinal space in vitreomacular interface conditions is evaluated. The study provides evidence of significant differences in preretinal space volume in eyes with vitreomacular adhesion and vitreomacular traction.